Chemical associations and mobilization of heavy metals in fly ash from municipal solid waste incineration. (April 2017) - Weibel, Gisela; Eggenberger, Urs; Schlumberger, Stefan; Mäder, Urs K.
Highlights: Characterization of fly ash and filter cake of three different large scale fly ash leaching processes. Systematic description of metal associations responsible for mobilization of metals during fly ash leaching. Factors controlling metal mobilization are pH-value, redox conditions, liquid-to-solid-ratio, temperature and reaction time. Hydrogen peroxide addition results in a significant increase of Pb and Cu depletion factor in filter cake. The study delivers valuable basis for definition of state of the art fly ash treatment in Switzerland. Abstract: This study focusses on chemical and mineralogical characterization of fly ash and leached filter cake and on the determination of parameters influencing metal mobilization by leaching. Three different leaching processes of fly ash from municipal solid waste incineration (MSWI) plants in Switzerland comprise neutral, acidic and optimized acidic (+ oxidizing agent) fly ash leaching have been investigated. Fly ash is characterized by refractory particles (Al-foil, unburnt carbon, quartz, feldspar) and newly formed high-temperature phases (glass, gehlenite, wollastonite) surrounded by characteristic dust rims. Metals are carried along with the flue gas (Fe-oxides, brass) and are enriched in mineral aggregates (quartz, feldspar, wollastonite, glass) or vaporized and condensed as chlorides or sulphates. Parameters controlling the mobilization of neutral and acidic fly ash leaching are pH and redox conditions, liquid to solid ratio, extraction time and temperature. Almost no depletion for Zn, Pb, Cu and Cd is achieved by performing neutral leaching. Acidic fly ash leaching results in depletion factors of 40% for Zn, 53% for Cd, 8% for Pb and 6% for Cu. The extraction of Pb and Cu are mainly limited due to a cementation process and the formation of a PbCu 0 -alloy-phase and to a minor degree due to secondary precipitation (PbCl2 ). The addition of hydrogen peroxide during acidic fly ash leaching (optimized acidic leaching) prevents this reduction through oxidation of metallic components and thus significantly higher depletion factors for Pb (57%), Cu (30%) and Cd (92%) are achieved. The elevated metal depletion using acidic leaching in combination with hydrogen peroxide justifies the extra effort not only by reduced metal loads to the environment but also by reduced deposition costs.